INTENTION TO USE QUICK RESPONSE CODE INDONESIAN STANDARD (QRIS) AS A PAYMENT TRANSACTION - Isa, Muhammad; Afandi, Ahmad; Lubis, Aswadi (Fakultas Ekonomi dan Bisnis Universitas Tanjungpura, 2025)
This study aims to determine the three pillars of SDT motivation that influence the use of technology and the four primary constructs of UTAUT that influence the intention to use QRIS for payment transactions. Data were collected using questionnaires distributed to millennials and Generation Z in Indonesia. A total of 150 respondents participated in this study. Structural Equation Modeling was used using SmartPLS version 3.0. The results showed that the three pillars of SDT motivation are autonomous variables that do not positively influence a person's motivation to use technology, whereas competence and relatedness do. Performance expectancy, social influence, and conditions that facilitate the intention to use QRIS for payment transactions positively differ from effort expectancy. The latter motivation positively influences the intention to use QRIS for payment transactions. This study integrates the SDT and UTAUT models, which have not been explored before, to measure motivation to use technology and intention to use QRIS. The results of this study can increase knowledge of digital literacy in Indonesia. JEL: G40, G10, O10.